2014
DOI: 10.3354/meps10931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grazing on distribution and recovery of harvested stands of Lessonia berteroana kelp in northern Chile

Abstract: Understanding the ecological factors regulating exploited natural communities is important in establishing conservation and management strategies. Since the 1960s, artisanal fishermen have harvested up to 300 000 dry tons yr −1 of wild populations of Lessonia spp. kelps. Adult kelps form a key habitat on the rocky shores of Chile, and benthic grazers regulate kelp populations by grazing or bulldozing microscopic and juvenile stages. To establish the role of the grazer assemblage in the recovery of kelp stands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 54 publications
1
24
0
4
Order By: Relevance
“…Notwithstanding, spatial variance in grazing effects hinges on the distribution of individuals when foraging and intrinsic individual variation, which are a direct function of population densities and resource spatial distribution [ 22 , 23 , 25 , 28 , 33 , 34 ]. For example, grazers with gregarious foraging patterns can create patchy distribution patterns of algal species, prescribing scales of spatial heterogeneity of the resident algal assemblage [ 11 , 23 , 25 , 35 ]. On one hand, herbivores of large body size have higher resource requirements and forage over broad areas, potentially homogenizing resource distribution [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, spatial variance in grazing effects hinges on the distribution of individuals when foraging and intrinsic individual variation, which are a direct function of population densities and resource spatial distribution [ 22 , 23 , 25 , 28 , 33 , 34 ]. For example, grazers with gregarious foraging patterns can create patchy distribution patterns of algal species, prescribing scales of spatial heterogeneity of the resident algal assemblage [ 11 , 23 , 25 , 35 ]. On one hand, herbivores of large body size have higher resource requirements and forage over broad areas, potentially homogenizing resource distribution [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the short spatial scale for prey behavioral response and following the strong consumptive effects that the herbivorous Fissurella limpets exert on the rocky inter‐tidal communities (Aguilera & Navarrete, ), we expect that the NCEs documented by this and earlier studies (Escobar & Navarrete, ; Manzur et al, ) should translate into strong ecological impacts, for example through diminished prey recruitment (Ellrich & Scorsati, ). In particular, given that NCEs were manifested as modifications of limpet movement, changes in foraging behavior under risk should cascade into differential consumer‐driven patterns of the inter‐tidal landscape (Díaz & McQuaid, ; Gosnell & Gaines, ; Oróstica, Aguilera, Donoso, Vásquez, & Broitman, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we found some experimental studies that deal directly with determining the impact of human harvesting and its propagation to community structure in intertidal rocky shore systems (e.g., kelp harvesting; Oróstica, Aguilera, Donoso, Vásquez, & Broitman, ; “human‐exclusion” experiments; Moreno, ; Castilla & Durán, ; Castilla, ; Moreno et al., ). No field experimental studies, however, deal with pollution in coastal habitats.…”
Section: Discussionmentioning
confidence: 99%